Self-consciousness and Self-expression of Qatari Female Students - Kajokaitė, Ieva (Acta Orientalia Vilnensia, 2006)
Center of Oriental Studies, Vilnius University This study sets out to outline the self-consciousness and self-expression of Qatari female students. The paper is based on a research carried out at the female section of the University of Qatar where Qatari girls were observed from September 2005 to May 2006. The recruited participants (14) were also interviewed at the later stage of the study. The results showed that, according to the axis of expression of the outward–inward female identity and the axis of autonomy–dependency, Qatari female students can be classified into three types: “beauteous Qataris,” “active Qataris” and “religious Qataris.” The paper critically discusses the main differences of the types. The main findings suggest that Qatari female students display a lot of superficial changes based on the imitation, which indicate deeper processes and the need to obtain more autonomy; education stimulates questioning of the moral norms imposed by society and family; Qatari female students start adopting a new interpretation of religious scriptures and dogmas from the woman-friendly perspective.